2012
DOI: 10.1038/mp.2012.15
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of potentially pathogenic SORL1 mutations in autosomal dominant early-onset Alzheimer disease

Abstract: Performing exome sequencing in 14 autosomal dominant early-onset Alzheimer disease (ADEOAD) index cases without mutation on known genes (amyloid precursor protein (APP), presenilin1 (PSEN1) and presenilin2 (PSEN2)), we found that in five patients, the SORL1 gene harbored unknown nonsense (n = 1) or missense (n = 4) mutations. These mutations were not retrieved in 1500 controls of same ethnic origin. In a replication sample, including 15 ADEOAD cases, 2 unknown non-synonymous mutations (1 missense, 1 nonsense) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
229
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(246 citation statements)
references
References 10 publications
5
229
1
Order By: Relevance
“…SORL1 encodes for the protein SorLA that belongs to a set of protein-trafficking molecules in the endocytic and retromer pathways and is implicated in modulating the production of Ab peptide [41]. These findings suggest that SORL1 may represent a genetic risk factor for AD, although these data need independent replication.…”
Section: Eofad With Mendelian Transmissionmentioning
confidence: 71%
See 1 more Smart Citation
“…SORL1 encodes for the protein SorLA that belongs to a set of protein-trafficking molecules in the endocytic and retromer pathways and is implicated in modulating the production of Ab peptide [41]. These findings suggest that SORL1 may represent a genetic risk factor for AD, although these data need independent replication.…”
Section: Eofad With Mendelian Transmissionmentioning
confidence: 71%
“…Recently, a study has detected mutations in the SORL1 gene in EOFAD patients [41]. SORL1 encodes for the protein SorLA that belongs to a set of protein-trafficking molecules in the endocytic and retromer pathways and is implicated in modulating the production of Ab peptide [41].…”
Section: Eofad With Mendelian Transmissionmentioning
confidence: 99%
“…Results from histopathological and epidemiological studies further substantiate the crucial role of this receptor in sporadic AD. Equally exciting is a recent report that mutations in SORL1 might even be the cause of autosomal dominant forms of early-onset AD (Pottier et al, 2012). Here, five missense mutations, one of which maps to the APP binding domain in SORLA, have been identified in familial cases of AD.…”
Section: Discussionmentioning
confidence: 95%
“…familial AD gene as well (11,26). Now, our studies identified the IR as a target for SORLA-mediated protein sorting in adipocytes.…”
Section: And H)mentioning
confidence: 95%